2020
DOI: 10.1021/acs.jced.9b01164
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Measurement and Data Correlation of Isatoic Anhydride in 12 Pure Solvents at Temperatures from 288.15 to 328.15 K

Abstract: The solid–liquid equilibrium solubility of isatoic anhydride in 12 pure solvents (methanol, ethanol, 1-propanol, isopropyl alcohol, methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, acetone, 2-butanone, acetonitrile, and 1,4-dioxane) at T = 288.15 to 328.15 K was measured by the gravimetric method under atmospheric pressure. Experimental results demonstrate that the mole fraction solubility of isatoic anhydride in these selected solvents increased with the increase of temperature, and the disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…The solute–solvent interaction can be reflected by polarity, which is an important index to characterize the strength of the intermolecular van der Waals force between the solvent and the solute . Besides, the hydrogen bonding interaction also contributes to the interactions between the solute and the solvents, which could be quantitatively represented by the summation of hydrogen bond donor/acceptor tendencies. , Generally, the formation of a hydrogen bond between the solvent and the solute can increase the solubility, and different abilities of hydrogen bonding may lead to discrepancies in dissolving capacity. , As shown in Figure , the molecule of NALP possesses one hydrogen donor (hydroxyl group) and three hydrogen acceptors (two carbonyl groups and one nitrogen atom), which means that NALP may form stronger hydrogen bonds between the solvents with the stronger capability of the hydrogen bond donor. It can be seen in Table that dichloromethane has the largest hydrogen bond donor propensity among the seven polar aprotic solvents, which could be the reason for the higher solubility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solute–solvent interaction can be reflected by polarity, which is an important index to characterize the strength of the intermolecular van der Waals force between the solvent and the solute . Besides, the hydrogen bonding interaction also contributes to the interactions between the solute and the solvents, which could be quantitatively represented by the summation of hydrogen bond donor/acceptor tendencies. , Generally, the formation of a hydrogen bond between the solvent and the solute can increase the solubility, and different abilities of hydrogen bonding may lead to discrepancies in dissolving capacity. , As shown in Figure , the molecule of NALP possesses one hydrogen donor (hydroxyl group) and three hydrogen acceptors (two carbonyl groups and one nitrogen atom), which means that NALP may form stronger hydrogen bonds between the solvents with the stronger capability of the hydrogen bond donor. It can be seen in Table that dichloromethane has the largest hydrogen bond donor propensity among the seven polar aprotic solvents, which could be the reason for the higher solubility.…”
Section: Resultsmentioning
confidence: 99%
“…Excluding intermolecular interactions, another two factors consisting of the molecular structure and viscosity may also influence the solubility behavior of NALP. Compounds with similar structures are more likely to be dissolved by each other, i.e., the rule of “like dissolves like”, , which could enhance the solubility of the solute. It can be observed that the solubility magnitudes in ketones (acetone and 2-butanone) are higher than those in esters (methyl acetate and ethyl acetate), which could be attributed to the same carbonyl groups possessed by the molecular structures of both ketones and NALP.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogen bond formed between a solute and a solvent has a significant effect on the solubility behavior, which could be quantitatively represented by the summation of hydrogen bond donation/acceptance tendencies. , In general, the formation of hydrogen bonds can increase solubility, and different hydrogen bonding capabilities may cause differences in solubility. , As shown in Figure , the molecule of NAM possesses two hydrogen donors (hydroxy and imino group) and two hydrogen acceptors (tow carbonyl groups), which shows that NAM is not only a hydrogen bond donor but also a hydrogen bond acceptor. NAM forms an O–H···O-type hydrogen bond in eight alcohol solvents, while O–H···O, N–H···O, O–H···N, N–H···N types of hydrogen bonds appear in aprotic solvents (except for dichloromethane).…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the solubility data and viscosity values of the selected solvents, it is found that the solubility in eight alcohol solvents, two ketone solvents, and two ester solvents decreased with the increase of viscosity. Compounds with similar structures can dissolve each other better and lead to the enhancement of the solubility, which is the principle of “like dissolves like”. , It can be inferred that the solubility in acetone and 2-butanone is higher than that in methyl acetate and ethyl acetate, which may be because the same carbonyl group existed in the ketones and NAM molecules. In addition, the high solubility of 1,4-dioxane may be speculated as follows: NAM can be used as a hydrogen bond donor and a hydrogen bond acceptor, leading to the formation of intramolecular hydrogen bonds, thus becoming a ring structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation